DUKUNGAN KELUARGA DAN PETUGAS KESEHATAN DALAM PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS KANATANG TAHUN 2016 - ATAMEHA, JOHANA BABANG (JURNAL KESEHATAN PRIMER, 2016)
Background: The less of breastfeeding for infants in Kanatang Health Centre, require precise handling. Mother's Milk (ASI) is an emulsion of fat in the solution of proteins, lactose and inorganic salts secreted by mothers mamary gland, which is useful as food for infants. Familys support and health care workers should be absolutely necessary to increase the rate of breastfeeding in Kanatang PHC in 2016. To determine the effect of familys support and health care workers for exclusive breastfeeding in Kanatang Public Health Centre. Methods:Descriptive Qualitative research, in order to determine the effect of familys support and health care workers on supporting factors in exclusive breastfeeding. Results of the study: The result showed that, for 33 respondents, there are 21 peoples (63.3%), have a good support levelby their family, and respondentwho have enough support level, there are 7 peoples (21.2%), and respondents who have less support level are 5 peoples (15.2%). All of the respondents said they received good support from health professional workers in case of exclusive breastfeeding. Conclusions:The conclusion is, most of the respondents received good support from family and health workers, so they are eager to give exclusive breastfeeding from 0-6 months of their baby.